Análisis de rotación del personal de la cooperativa JEP, agencia Loja II, periodo 2022-2023 y propuesta de mejora. - Campoverde Jarrín, Carlos Augusto (2024)
Globally, in both public and private organizations, the Human Resources department is currently facing the problem of staff turnover. This is because people are hired for a job for a certain period of time, usually short, and then they resign or are promoted. The objective of this research is to carry out an exhaustive analysis of the rotation of human talent in the Loja II Agency of the JEP Cooperative. The present research was carried out in the JEP Cooperative (Progressive Ecuadorian Youth), located in the province and canton of Loja, it had a mixed approach since it allowed the collection, interpretation and analysis of data, both quantitative and qualitative in a single approach, facilitating the understanding of the realities of the research problem more efficiently. 36 employees and workers were surveyed and the two variables (RP) were tabulated in the results; As relevant results, we have that the main cause of rotation is the institutional need and the willingness to assume new responsibilities, performance evaluations are prevailing. The departments that have rotated the most personnel are: cashier staff, service staff and finally credit staff. In conclusion, the poor organizational and functional structure of the JEP Cooperative is denoted, which allows us to determine that the organizational structure must be reviewed and modified. Another factor to consider is that the functions of employees and workers are not well defined, which generates discomfort and demotivation among staff and therefore poor performance in their duties.